Widening the Spaces of Selection: Evolution along Sublethal Antimicrobial Gradients - Fernando Baquero (American Society for Microbiology, 2014)
ABSTRACT The work of Gullberg et al. (E. Gullberg, L. M. Albrecht, C. Karlsson, L. Sandegren, D. I. Andersson, mBio 5:e01918-14, 2014) indicates that extremely low concentrations of antibiotics and heavy metals are able to compensate for the cost of harboring a plasmid encoding resistances to these inhibitors. Therefore, the “spaces of selection” for plasmids encoding antibiotic or metal resistance along gradients of antimicrobial agents might be huge, and in wide spaces a high number of bacterial cells are exposed to the selective effects. These spaces are even broader if several inhibitors are simultaneously present. Probably very small inhibitor concentrations in the environment, including in sewage and other water bodies, are sufficient to ensure the maintenance and spread of this kind of multiresistance plasmid.